Phenanthridine Sulfonamide Derivatives as Potential DPP-IV Inhibitors: Design, Synthesis and Biological Evaluation - Khalaf, Reema A.; Alqazaqi, Shorooq; Aburezeq, Maram; Sabbah, Dima; Albadawi, Ghadeer; Sheikha, Ghassan Abu (Current Computer - Aided Drug Design, 2022)
Background: Diabetes mellitus is a chronic metabolic disorder, characterized by hyperglycemia over a prolonged period, disturbance of fat, protein, and carbohydrate metabolism, resulting from defective insulin secretion, insulin action or both. Dipeptidyl peptidase-IV (DPP-IV) inhibitors are relatively a new class of oral hypoglycemic agents that reduce the deterioration of gutderived endogenous incretin hormones secreted in response to food ingestion to stimulate the secretion of insulin from beta cells of the pancreas. Objective: In this study, synthesis, characterization, and biological assessment of twelve novel phenanthridine sulfonamide derivatives 3a-3l as potential DPP-IV inhibitors were carried out. The target compounds were docked to study the molecular interactions and binding affinities against the DPP-IV enzyme. Methods: The synthesized molecules were characterized using 1H-NMR, 13C-NMR, IR, and MS. Quantum-polarized ligand docking (QPLD) was also performed. Results: In vitro biological evaluation of compounds 3a-3l reveals comparable DPP-IV inhibitory activities ranging from 10%-46% at 100 μM concentration, where compound 3d harboring ortho- fluoro moiety exhibited the highest inhibitory activity. QPLD study shows that compounds 3a-3l accommodate DPP-IV binding site and form H-bonding with the R125, E205, E206, S209, F357, R358, K554, W629, S630, Y631, Y662, R669, and Y752 backbones Conclusion: In conclusion, phenanthridine sulfonamides could serve as potential DPP-IV inhibitors that require further structural optimization in order to enhance their inhibitory activity.
Keywords: QPLD